A thermodynamic framework for unified continuum models for the healing of damaged soft biological tissue. (January 2022) - Zuo, Di; He, Yiqian; Avril, Stéphane; Yang, Haitian; Hackl, Klaus
Abstract: When they are damaged or injured, soft biological tissues are able to self-repair and heal. Mechanics is critical during the healing process, as the damaged extracellular matrix (ECM) tends to be replaced with a new undamaged ECM supporting homeostatic stresses. Computational modeling has been commonly used to simulate the healing process. However, there is a pressing need to have a unified thermodynamics theory for healing. From the viewpoint of continuum damage mechanics, some key parameters related to healing processes, for instance, the volume fraction of newly grown soft tissue and the growth deformation, can be regarded as internal variables and have related evolution equations. This paper is aiming to establish this unified framework inspired by thermodynamics for continuum damage models for healing of soft biological tissues, in which we introduce for the first time the coupled description of damage/healing and growth/remodeling based on thermodynamic considerations. Therefore, this new model is more concise and offers a universal approach to simulate the healing process. Three numerical examples are provided to demonstrate the effectiveness of the proposed model, which are in good agreement with the existing works, including an application for balloon angioplasty in an arteriosclerotic artery with a fiber cap. Highlights: A unified continuum damage model inspired by thermodynamics for the healing of soft biological tissues is presented. The coupled description of damage/healing and growth/remodeling is strictly based on thermodynamic considerations. The effectiveness of the proposed model is illustrated through three numerical examples.